Integrating Engineering, Automation, and Intelligence to Catalyze the Biomedical Translation of Organoids (Adv. Biology 8/2021). Issue 8 (6th August 2021) - Ma, Shaohua; Zhao, Haoran; Galan, Edgar A.
Abstract : Organoids Biomedical Translation In article 2100535, Ma and co‐workers describe their perspective on the engineering elements to promote organoid applications in biomedical translation. "Organoid engineering" comprises the conceptual modules of high‐throughput organoid production with reduced variability, automated culturing in a hyper‐parallel manner, and intelligent organoid evaluation by learning algorithms to process multi‐modality data, and finally, "instrumentation" to catalyze biomedical translation of organoid technologies.